Characterization of aquilaria malaccensis callus cells using SEM and somatic embryogenesis associated genes identification - Mohd Syafik, Mohamad Hamdan; Aimi Wahidah, Aminan; Siti Hajar Noor, Shaarani; Saiful Nizam, Tajuddin (IOP Publishing Ltd., 2020)
Aquilaria malaccensis or gaharu is one of Malaysia's top tropical resources that is being protected and conserved. Somatic embryogenesis is a plant tissue culture method used most extensively in commercial micropropagation systems and conservation purposes. This study aims to optimize callus induction techniques for somatic embryogenesis study using Scanning Electron Microscope (SEM) and Polymerase Chain Reaction (PCR) analysis. In this study, callus was induced on Murashige and Skoog's (MS) medium supplemented with a combination of plant growth regulators and optimized parameters (explant used, sterilization techniques, media content, pH media, plant growth regulators, incubation condition, and incubation temperature). The cells were subcultured for long-term callus maintenance and subjected to SEM analysis for somatic embryogenesis confirmation. Four set of genes associated to somatic embryogenesis (SERK, BBM, LEC1, and WOX) were studied based on National Centre for Biotechnology Information database and literatures. The data obtained were used for primer design and gene amplification using 3 different tissues (leaf, stem, callus).The highest frequencies of callus induction were observed on Murashikage and Skoog medium supplemented with 6-Benzylaminopurine and 1-Naphthaleneacetic acid together with optimized growth parameters. SEM analysis showed embryogenic characteristics in cells of the yellow compact calli evidenced by the presence of small and isodiametric cells. Only SERK gene was successfully amplified and enable to proceed with in silico analysis. This study provides fundamental results for genetic conservation effort of A. malaccensis related to somatic embryogenesis study.